Legal Status and Rights of Children from Mixed Marriages Abroad that are not Registered in the Indonesian Civil Registry - Andyna Susiawati Achmad; Paula Paula; Astrid Athina Indradewi (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze (1) the registration of mixed marriages conducted abroad in the Indonesian Civil Registry and (2) the rights and legal status of children from mixed marriages abroad who are not registered with the Indonesian Civil Registry. Technology development has increased interactions between citizens of different countries, resulting in mixed marriages. The prospective husband and wife from various nationalities are subject to the laws of their respective countries. In the international realm, there are differences between Indonesian marriage laws and those of other countries, both in material and procedural aspects. The research method used is normative juridical. The findings of this study indicate that mixed marriages conducted abroad can be registered in Indonesia by fulfilling administrative requirements. Children from mixed marriages abroad who are not registered in Indonesia are considered Indonesian citizens and have rights as children born out of wedlock unless acknowledged by their father or it can be proven that the child has a blood relationship with the father.